2017
DOI: 10.22159/ijpps.2017v9i11.19444
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicines as Neuroprotective Agent: A Mechanistic Approach

Abstract: Neurodegeneration refers to a condition of neuronal death occurring as a result of progressive disease of long-term and is becoming a major health problem in the 21st century. Neurons degenerated are not replaced resulting in a cognitive loss, many neurodegenerative disorders, such as schizophrenia, depression, Alzheimer's disease (AD), dementia, cerebrovascular impairment, seizure disorders, head injury, parkinsonism. The common pathology of neurodegeneration includes deposition of misfolded proteins such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 117 publications
1
17
0
Order By: Relevance
“…Histopathological studies were shown as appeared as shrunken and decreased number of the pyramidal cells [39]. These results inferred with our study and suggest that the herbal plants could be a valuable source of drug against NDD which will prove through highthroughput screening for further drug discovery fields [40]. Our results exhibit that elevated BDNF level in drug-treated group may be implied with prevention of cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
“…Histopathological studies were shown as appeared as shrunken and decreased number of the pyramidal cells [39]. These results inferred with our study and suggest that the herbal plants could be a valuable source of drug against NDD which will prove through highthroughput screening for further drug discovery fields [40]. Our results exhibit that elevated BDNF level in drug-treated group may be implied with prevention of cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
“…Protein misfolding and their accumulation inside or outside of neurons are the key pathological feature in several neurodegenerative diseases, including Alzheimer's, and Parkinson's Huntington's disease. Herbal medicines are regarded as effective and promising sources of potential neuroprotective agents because of their cognitive benefits and more significantly, their mechanisms of action with respect to the fundamental pathophysiology of the diseases [45]. HPTLC method was developed using the combination of three solvents as a mobile phase, i.e., toluene-chloroform-methanol (5:…”
Section: Extraction Methods For Curcuminmentioning
confidence: 99%
“…The [13]. Anxiolytic agents increase the motor activity, which manifests an increase in the time spent by the animal in the open arms of EPM [14].…”
Section: Anxiolytic Responsementioning
confidence: 99%